The Impella CP device for acute mechanical circulatory support in refractory cardiac arrest. (March 2017) - Vase, Henrik; Christensen, Steffen; Christiansen, Aage; Therkelsen, Christian Juhl; Christiansen, Evald Høj; Eiskjær, Hans; Poulsen, Steen Hvidtfeldt
Abstract: Introduction: Mechanical circulatory support may be considered as a therapeutic option in selected patients with refractory cardiac arrest (rCA). Animal studies suggest a potential role for the Impella ® left ventricular assist device in this setting, but so far no human data have been published. Methods: Eight patients with rCA were treated with the Impella CP ® device at our institution from November 2014 to October 2015. The Impella CP ® was used at the discretion of the treating physicians in patients with rCA and pulseless electrical activity with presumed primary left ventricular failure. These patients were compared to 12 patients with cardiogenic shock also treated with the Impella device during the same period. Results: All cardiac arrests were witnessed with a no-flow time of 0 min, six in-hospital and two out-of-hospital. Low-flow time was 50 ± 52 min (SD). The Impella device was successfully inserted in all patients with rCA and circulation was re-established. Survival rate to hospital discharge with good neurological outcome was similar among patients with rCA and cardiogenic shock treated with the Impella device (50% vs. 58%). Major vascular complications after Impella insertion occurred more frequently among patients with rCA compared to patients with cardiogenic shock (50% vs. 0%, P < 0.05). Conclusion: Mechanical support with the Impella CP ® device is a feasible and promising treatment option for selected patients with rCA. Further studies are warranted to determine the full potential and optimal patient selection compared to other modalities of mechanical circulatory support.